The Trend of COVID-19 Pandemic in India: A Methodical Comparison with Italy, UK, and the US - Mantri, Neha; Gupta, Manoj Kumar; Bhardwaj, Pankaj; Goel, Dhanesh Akhil; Saurabh, Suman; Misra, Sanjeev (National Journal of Community Medicine, 2022)
Introduction: To statistically compare the trends of epidemiological indicators of COVID-19 in India with Italy, the UK, and the US. Methodology: In this descriptive analysis, epidemiological indicators were calculated and their trends were plotted and compared statistically. Regression analysis was done to predict the fatalities. Results: The trends of total and active cases per million populations are rising in India and US, while Italy has achieved the plateau in the total cases per million populations, and active cases have been sharply declining with time. The UK is about to achieve the same. India has remained far behind the other three countries in the number of tests per million populations (p<0.05). In the initial phase, the test positivity rate of India was quite lower but has overtaken Italy and UK. India has always reported a higher recovery rate than US and lower than Italy. CFRs have achieved a plateau in Italy and UK, in US it is declining, while it remained almost constant in India throughout the pandemic. Testing was a significant covariate in predicting the fatalities. Conclusions: India was able to manage the initial phase of this pandemic due to early and strict government interventions and strong public health responses.